2004
DOI: 10.1016/j.str.2004.09.011
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into FAK Signaling and Localization Based on Detection of a FAT Domain Folding Intermediate

Abstract: Mounting evidence suggests that the focal adhesion targeting (FAT) domain, an antiparallel four-helix bundle, exists in alternative conformations that may modulate phosphorylation, ligand binding, and the subcellular localization of focal adhesion kinase (FAK). In order to characterize the conformational dynamics of the FAT domain, we have developed a novel method for reconstructing the folding pathway of the FAT domain by using discrete molecular dynamics (DMD) simulations, with free energy constraints derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 53 publications
4
69
0
Order By: Relevance
“…An example of the change in HX behavior as a function of protein concentration is shown in Figure 5B. As the protein concentration was increased, the apparent number of amide hydrogens exchanging through the fast, k f , process decreased and the number exchanging through the slow, k s , process increased for peptide 26-35, segment 31-47, and peptide [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. No reliable trends were observed for the k i1 and k i2 processes for these peptides or segments.…”
Section: Experimental Analysismentioning
confidence: 99%
“…An example of the change in HX behavior as a function of protein concentration is shown in Figure 5B. As the protein concentration was increased, the apparent number of amide hydrogens exchanging through the fast, k f , process decreased and the number exchanging through the slow, k s , process increased for peptide 26-35, segment 31-47, and peptide [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. No reliable trends were observed for the k i1 and k i2 processes for these peptides or segments.…”
Section: Experimental Analysismentioning
confidence: 99%
“…In recent studies, Gsponer et al [171] and Dixon et al [172] [165]. Besides HX methods, the site-specific structural information obtained from other NMR-based techniques such as relaxation dispersion spectroscopy [173], has also been incorporated into MD simulations to study weakly-populated folding intermediates [174].…”
Section: Protein Intermediate Statesmentioning
confidence: 99%
“…Several protein models that have striking predictive power have been developed in the last six years [15,17,18,22,25]. In most cases, predictions made using these models were not validated by experiments at the time of publication.…”
Section: Dmdmentioning
confidence: 99%
“…The phosphorylation-competent domain states of FAT are weakly populated and, therefore, are not amenable to structural determination by NMR. Using the developed method, we have identified these weakly populated intermediate states of the FAT domain and found that Y926, which belongs to helix 1 of the four-helix bundle that comprises the FAT domain, is phosphorylated in these states [22]. A similar approach has also been proposed by Vendruscolo et al [42], who has related the number of native contacts per residue to its equilibrium hydrogenexchange-protection factor and reconstructed the ensemble of protein conformations that are consistent with the experimental condition.…”
Section: Catching Evasive Protein Statesmentioning
confidence: 99%
See 1 more Smart Citation